RISK AS THE MAIN CONDITION OF INSURANCE IN INVESTMENT ACTIVITIES - Eshchanova Dauletbike Ametbekovna (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the legal concept of